2019
DOI: 10.1051/e3sconf/20199107014
|View full text |Cite
|
Sign up to set email alerts
|

Structure and physical properties of sulfur with nanoscale carbon modifiers

Abstract: It is known that sulfur-extended asphalt is of improved operational properties. Binders with higher content of polymeric sulfur are characterized by higher operational properties. Unfortunately, many sulfur modifiers are volatile and toxic. The objective of article is to investigate the structure of sulfur with admixtures of saturated aliphatic hydrocarbon and two types of nanoscale carbon modifiers. It was shown that such admixtures lead to formation of the fine-crystalline structure of high uniformity; avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The authors of works [ 1 , 2 , 3 , 4 , 5 , 6 ] have shown that the use of sulfur as a modifier for asphalt concrete is a promising direction, allowing the expansion of the temperature range of operation of asphalt concrete pavements in the area of high positive temperatures. In addition, in works [ 5 , 6 , 7 ] it is shown that the introduction of sulfur provides a decrease in the amount of bitumen in the asphalt concrete mixture, as well as a decrease in the temperature of preparation and laying The use of sulfur improves not only the operational properties of sulfur asphalt concrete (SEA) but also the technological properties of the mixture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of works [ 1 , 2 , 3 , 4 , 5 , 6 ] have shown that the use of sulfur as a modifier for asphalt concrete is a promising direction, allowing the expansion of the temperature range of operation of asphalt concrete pavements in the area of high positive temperatures. In addition, in works [ 5 , 6 , 7 ] it is shown that the introduction of sulfur provides a decrease in the amount of bitumen in the asphalt concrete mixture, as well as a decrease in the temperature of preparation and laying The use of sulfur improves not only the operational properties of sulfur asphalt concrete (SEA) but also the technological properties of the mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The values of the empirical coefficients of function (1) for the first section of the kinetics and the linear equation (C(t) = b + kt, where C(t) is the concentration of calcium and magnesium ions in the aqueous extract; k, b are empirical coefficients) for the second section are given in Table 5. Analysis of the data in Table 5 shows that in the first section, the dependences of the coefficients Cmax = f(S), α = f(S), and n = f(S) on the sulfur content in SBB are linear.…”
mentioning
confidence: 99%